2014
DOI: 10.1002/adma.201305845
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar MoTe2 Transistors and Their Applications in Logic Circuits

Abstract: We report ambipolar charge transport in α-molybdenum ditelluride (MoTe2 ) flakes, whereby the temperature dependence of the electrical characteristics was systematically analyzed. The ambipolarity of the charge transport originated from the formation of Schottky barriers at the metal/MoTe2 contacts. The Schottky barrier heights as well as the current on/off ratio could be modified by modulating the electrostatic fields of the back-gate voltage (Vbg) and drain-source voltage (Vds). Using these ambipolar MoTe2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
365
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(389 citation statements)
references
References 38 publications
21
365
2
1
Order By: Relevance
“…When a negative V bias is applied to the WSe 2 amplifier (Fig. 5c), in the positive phase of V ac , I ds increases/ decreases as V GS decreases/increases, so the voltage drop across the off-chip resistor will increase/decrease, respectively 46,47 . As a consequence, the corresponding V out will decrease/increase, which exhibits the same phase as the input signal.…”
Section: Resultsmentioning
confidence: 99%
“…When a negative V bias is applied to the WSe 2 amplifier (Fig. 5c), in the positive phase of V ac , I ds increases/ decreases as V GS decreases/increases, so the voltage drop across the off-chip resistor will increase/decrease, respectively 46,47 . As a consequence, the corresponding V out will decrease/increase, which exhibits the same phase as the input signal.…”
Section: Resultsmentioning
confidence: 99%
“…1b, the measured height of the MoTe 2 flake was 4 nm, corresponding to six layers. 28,29 Figure 1d depicts the Raman spectra of the MoTe 2 flake, which shows the characteristic in plane E . [24][25][26][27][28][29] The Raman spectra for MoS 2 flake is shown in Fig.…”
Section: Experimental Results Without Lightmentioning
confidence: 99%
“…Most MTe 2 ‐based FETs have been reported to possess a carrier mobility of 1–68 cm 2 V −1 s −1 and large on/off ratios of 10 4 –10 6 16, 22, 75, 98, 166, 167, 168. Pradhan et al reported hole‐doped MoTe 2 field‐effect transistors ( Figure 6 a) with a saturated carrier mobility of up to 20 cm 2 V −1 s −1 under a suitable bias at room temperature.…”
Section: Applications For 2d Optoelectronic and Electronic Devicesmentioning
confidence: 99%